Reflexiones en torno al equilibrio económico financiero - Nalvarte Salvatierra, Pierre (2021)
Financial economic equilibrium is a concept that can be objectively determined, from a financial mathematical point of view, beyond what is prescribed by current legal regulations. It is important to be aware of this. Even when a rule or a contractual clause establishes a mechanism for restoring the economic and financial equilibrium, it may not be achieved, because for this, strictly speaking, the expected profitability or the net present value would have to be maintained, in accordance with the applicable cost of capital. The true economic and financial equilibrium is considered when evaluating an addendum to a PPP contract or when structuring a new PPP. If a mechanism is stipulated in a future contract that truly seeks to reestablish the economic and financial equilibrium, this would have to materialize by preparing a cash flow and observing the IRR or NPV, even if this is more complex.